2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2019
DOI: 10.1109/cvprw.2019.00342
|View full text |Cite
|
Sign up to set email alerts
|

Biometric Template Storage With Blockchain: A First Look Into Cost and Performance Tradeoffs

Abstract: We explore practical tradeoffs in blockchain-based biometric template storage. We first discuss opportunities and challenges in the integration of blockchain and biometrics, with emphasis in biometric template storage and protection, a key problem in biometrics still largely unsolved. Blockchain technologies provide excellent architectures and practical tools for securing and managing the sensitive and private data stored in biometric templates, but at a cost. We explore experimentally the key tradeoffs involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Delgado-Mohatar et al [24] presented the advantages and limitations of using blockchain in biometrics and vice versa. In continuation to the first work, Delgado-Mohatar et al [44] analysed the growth of biometric system based on blockchain. The authors mainly focused on storing the biometric templates in the blockchain by using on-chain, direct hashing and Merkle-trees.…”
Section: Blockchain For Biometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delgado-Mohatar et al [24] presented the advantages and limitations of using blockchain in biometrics and vice versa. In continuation to the first work, Delgado-Mohatar et al [44] analysed the growth of biometric system based on blockchain. The authors mainly focused on storing the biometric templates in the blockchain by using on-chain, direct hashing and Merkle-trees.…”
Section: Blockchain For Biometricsmentioning
confidence: 99%
“…In continuation to the first work, Delgado‐Mohatar et al . [44] analysed the growth of biometric system based on blockchain. The authors mainly focused on storing the biometric templates in the blockchain by using on‐chain, direct hashing and Merkle‐trees.…”
Section: Related Workmentioning
confidence: 99%
“…Each string can specify a portion of the user's data to which third party viewers are allowed to access. Delgado-Mohatar et al explored practical tradeoff in blockchain-based biometric template storage [24]. They had recently experimentally studied the fundamental tradeoffs involved in the integration of Biometric (such as face and handwritten signatures) template storage with the Ethereum blockchain [25], including latency, processing time, gas cost and recognition rate.…”
Section: Related Workmentioning
confidence: 99%
“…As a result, the authors found that straightforward schemes for data storage in the blockchain may be prohibitive for biometric template storage using state-of-the-art biometric methods. Still, the system based on Merkle trees had an excellent cost-performance tradeoff; however, no specific security and privacy protection scheme other than digital signature and hashing has been considered in [24]. In this work, we try to provide a general security and privacy-preserving approach to blockchain-Oracle combined applications by using homomorphic encryption techniques.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, encrypting the fingerprint template after pre-processing is essential before uploading it to IPFS. Data hashing technique by the IPFS is somewhat unsecured, because data can be retrieved if in possession of the hash [15]. Accordingly, by implementing the symmetric key; advanced encryption standard (AES) or any other encryption algorithm to files before uploading to the IPFS solves the issue of system viability when compromised by a malicious node or attacker is rectified.…”
Section: Introductionmentioning
confidence: 99%